Care and compassion in capitalism - Yalkin, Cagri; Özbilgin, Mustafa F. (Emerald Publishing Limited, 2024)
Capitalism and its many manifestations have a marked impact on the way care and compassion are defined and experienced internationally. Addressing a gap in the examination of market-centric and individual-focused aspects of care, this volume of International Perspectives on Equality, Diversity and Inclusion brings together interdisciplinary insights from across the social sciences to enrich the debate in the field of business and management around the treatment of care, compassion and capitalism. Considering different care arrangements such as parental care, elder care, care of youth and community and self-care, chapters investigate how capitalist ideologies impact markets, organisations, relationships and labour. Calling for a 'responsibilisation' to curb the corrosive impact of the current market, Care and Compassion in Capitalism offers not only a critique of the capitalist condition but also interrogates the extent to which it is possible to tame and overcome the power inequities induced in the interplay of care, compassion and capitalism.
Keywords: Capitalism.; Business & Economics -- Free Enterprise & Capitalism.; elektronické knihy; electronic books